Antagonistic effects of dietary Moringa oleifera on hemato‐biochemical and oxidative stress of lead nitrate intoxicated Nile tilapia, Oreochromis niloticus. (19th July 2021) - Kiran Kumar, E; Midhun, Sebastian Jose; Vysakh, A.; James, T.J.
Abstract: Heavy metal toxicity is a major threat to the aquatic environment as well as organisms. Therefore, the present study aims to assess the potential effect of  Moringa oleifera  flower in enhancing growth, as well as on antioxidant system in  Oreochromis niloticus  (Tilapia fish), challenged/non‐challenged with a salt of heavy metal lead (Pb). 4.02ppm of Pb(NO3 )2 (10% of 96 hr‐LC50 ) was used for challenge tests. Bioaccumulation studies have confirmed the accumulation of Pb in the fish liver. After 30 days of the experiment, growth parameters, haematological and biochemical parameters, and antioxidant activity in the fish were assessed. Groups fed with  Moringa oleifera  flower diets could withstand the physiological stress and ameliorated the depleted antioxidant enzyme activity in the liver. Histological studies were revealed that the test group supplemented with flower ingredients was protected well from heavy metal assault while the control group showed necrosis and damage to the liver. Expression of antioxidant genes was also upregulated in the flower diet supplemented group. A non‐Pb exposed group which were under flower diet showed significant body growth compared to that of the control group. The results from the study revealed that the heavy metal toxicity could be alleviated in fish by Moringa oleifera flower supplementation in the diet.